The Wrong Tool for the Right Job: Composition on 8-bit Machines - Tobias Banks (INSAM)
An artist’s medium can inspire them to reach new heights with its possibilities or curtail their ambitions with its limitations—but, ultimately, it is what gives shape to their artistic vision. Few artistic mediums exemplify the conflict between possibilities and limitations, and the sheer ingenuity of artists as they balance these two forces, as well as computer music does. This paper will delve into the rich tradition of demoscene and videogame music, that flourished in the early days of personal computers and gaming consoles, to examine how the hardware used by different composers affected their processes. This paper discusses the technical specs and rich library of music of three very different pieces of hardware: the Commodore 64, the ZX Spectrum, and the Nintendo Entertainment System. The C64, with its powerful and revolutionary “SID chip” sound card, demonstrates the amazing potential computer music offers to those determined enough to surmount the technical challenges. The ZX Spectrum, with its one-channel beeper speaker, shows how a resourceful artist can wring brilliance from even the most limited of mediums. And the NES, with its five channels of pure nostalgia, teaches us that a couple of square waves and some heart can inspire a generation.